Disidencias sexuales en Argentina: tres películas del siglo XXI. Non-hegemonic sexualities in Argentina: three movies of the 21st Century - Peidro, Santiago (Latinoamérica. Revista de Estudios Latinoamericanos, 2017)
Este trabajo plantea una aproximación crítica al estudio de las disidencias sexuales en Argentina y da cuenta de la insuficiencia de abordarlas desde el modelo gay importado de Estados Unidos. Este estudio de las identidades sexuales no hegemónicas en el sur del continente americano considera algunos aportes de los ensayistas Néstor Perlongher y Pedro Lemebel y fundamentalmente se sostiene del análisis de tres textos fílmicos argentinos del siglo xxi. Abstract: This article proposes an approximation to the study of non-hegemonic sexualities in Argentina considering the problem of addressing them from a standardized gay model imported from the United States. The study of non-hegemonic sexual identities in the South of Latin-America will be carried out considering Néstor Perlongher and Pedro Lemebel’s contributions and fundamentally, by analyzing three Argentine movies of the 21st Century.